2018
DOI: 10.1159/000495554
|View full text |Cite|
|
Sign up to set email alerts
|

Long Noncoding RNA FER1L4 Suppresses Tumorigenesis by Regulating the Expression of PTEN Targeting miR-18a-5p in Osteosarcoma

Abstract: Background/Aims: Novel long non-coding RNA Fer-1-like protein 4 (FER1L4) has been reported to play crucial regulatory roles in tumor progression. However, its clinical significance and biological role in osteosarcoma (OS) is completely unknown. The aim of the present study was to investigate the role of FER1L4 in OS progression and the underlying mechanism. Methods: We analyzed the expression levels of FER1L4 in tissues of OS patients and cell lines via quantitative RT-PCR (qRT-PCR). The effect of FER1L4 on ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…The exception is a report about the Fer1L4 possible role in glioma progression, where high expression of Fer1L4 was associated with a poor disease prognosis [162]. Fer1L4 exerts its function via the PTEN/PI3K/AKT signaling pathway [161,163,164]. The role of this pathway in tumorigenesis was described in detail [165].…”
Section: Fer1l4-a Non-muscle Ferlin Long Non-coding Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…The exception is a report about the Fer1L4 possible role in glioma progression, where high expression of Fer1L4 was associated with a poor disease prognosis [162]. Fer1L4 exerts its function via the PTEN/PI3K/AKT signaling pathway [161,163,164]. The role of this pathway in tumorigenesis was described in detail [165].…”
Section: Fer1l4-a Non-muscle Ferlin Long Non-coding Rnamentioning
confidence: 99%
“…PTEN is known as a tumor suppressor inhibiting PI3K/AKT proliferation signaling. Downregulation of Fer1L4 expression correlated with decrease of the level of PTEN [164,166], while Fer1L4 overexpression inhibited the PI3K/AKT signaling pathway [67,163]. Thus, the Fer1L4 RNA may serve as a competing endogenous RNA and regulate the expression of PTEN via miRNA-mediated mechanisms inhibiting cancer cell proliferation and metastasis [164,166].…”
Section: Fer1l4-a Non-muscle Ferlin Long Non-coding Rnamentioning
confidence: 99%
“…Studies on FER1L4 suggested that FER1L4 mainly exerted its function via sponging miRNAs in cancer cells [18,28]. We predicted that FER1L4 sequence harbored binding site for miR-92a-3p.…”
Section: Discussionmentioning
confidence: 89%
“…The most well-characterized role of FER1L4 is its tumor suppressor function as a negative regulator of AKT signaling in cancers [30,31]. Many studies showed that FER1L4 inactivated AKT signaling to suppress cancer progression including osteosarcoma, lung cancer, hepatocellular carcinoma and endometrial carcinoma [28,38,39]. FER1L4 also repressed esophageal squamous cell carcinoma proliferation [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation